Extraction and physico-chemical and functional characterisation of hydrocolloids from tamarillo (Solanum betaceum cav.) fruit - Gannasin, Sri Puvanesvari (2015)
Amongst the fruits, only red tamarillo (Solanum betaceum Cav.) contains both polar (anthocyanins) and non-polar (carotenoids) pigments in its mesocarp. The ability to retain both polar and non-polar pigments in the mesocarp could be related to the unique properties of its hydrocolloids. To understand the hydrocolloid-pigment interaction in the fruit, information on physico-chemical and functional properties of the hydrocolloids is required. Therefore, hydrocolloids from the anthocyanin-rich seed mucilage fraction of the tamarillo and its carotenoid-rich pulp fraction were extracted and characterised. Water and 1% citric acid were able to extract the seed mucilage hydrocolloid from tamarillo puree while pulp hydrocolloid was extracted from the puree using 72% ethanol and 20 mM HEPES buffer. The solubility of seed mucilage hydrocolloid in water was almost 90% compared to that of pulp hydrocolloid (28%). Hydrophilic seed mucilage hydrocolloid was mainly composed of uronic acids (> 65%) apart from the major neutral sugars arabinose, galactose and rhamnose. Meanwhile, the less polar pulp hydrocolloid was predominantly constituted of glucose, galactose, arabinose and xylose and approximately 20-30% of uronic acids. Molecular weight and radius of gyration of seed mucilage hydrocolloid (~ 2 x 105 g/mol; ~ 50 nm) were lower than that of pulp hydrocolloid (~ 2 x 107 g/mol; ~ 120 nm). Based on physicochemical properties of the hydrocolloids, it was deduced that seed mucilage hydrocolloid was primarily composed of arabinogalactan protein-associated low methoxyl pectin whereas the pulp hydrocolloid was composed of hemicellulosic polysaccharides. Rheological and functional characterisations of the hydrocolloids were also performed. Oscillation frequency sweep test of 2% (w/v) seed mucilage hydrocolloid revealed its liquid-like behaviour in water while the pulp hydrocolloid exhibited gel-like behaviour at 2% (w/v) in water. The water-holding capacity of pulp hydrocolloid (~ 25 g water/g sample) was almost five folds higher than that of seed mucilage hydrocolloid while oil-holding capacity of pulp hydrocolloid was double the value of seed mucilage hydrocolloid (~ 2 g oil/g sample). The emulsifying activity and emulsion stability of pulp hydrocolloid were 90% and 95%, respectively, which were exceptional in comparison to that of other commercial hydrocolloids studied. Meanwhile, the foaming capacity of seed mucilage hydrocolloid (~35%) was higher than that of thirteen commercial hydrocolloids studied except for bovine gelatine (62%). Nevertheless, the seed mucilage hydrocolloid had better foam stability (80%) than bovine gelatine (11%) after 2 h of foam formation. In addition to good technological functionalities, 2% (w/v) of tamarillo pulp hydrocolloid possessed higher bile acid-binding capacity (38%) than 2% (w/v) of commercial oat fibre (27%). In vitro fermentation of the hydrocolloids using gut microbiota showed that seed mucilage hydrocolloid increased the number of lactobacilli and bifidobacteria more than the pulp hydrocolloid. Short chain fatty acids (acetate, propionate and butyrate) formation reduced the pH in the batch culture fermentation units which further indicated the prebiotic activity of the hydrocolloids. In conclusion, red tamarillo mesocarp contains two types of hydrocolloids with unique properties: (i) hydrophilic arabinogalactan protein-associated low methoxyl pectin in the anthocyanin-rich seed mucilage and (ii) less polar hemicellulosic polysaccharides in the carotenoid-rich pulp.